Reforming Spending Policy and Its Impact on Indonesia’s Economy: The Case of Fuel Subsidy and Infrastructure - Anas, Muhammad (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2019)
The quality of Indonesia’s infrastructure up until 2014 was considered uncompetitive, and one of the reasons was that there was not enough money spent on infrastructure, and too much on fuel subsidy. In November 2014, the government of Indonesia decided to cut the expenditure for fuel subsidy and reallocate the money to invest on public services. This study was conducted with the intention to quantify the impact of the program on economic growth and income distribution in Indonesia using Social Accounting Matrix (SAM) model. Simulation results indicated that the impact from social and human capital infrastructure was bigger than that of economic infrastructure, although the simulation for both categories resulted in an increase of sectoral output and domestic income. Therefore, improving infrastructure, especially social, is vital to stimulate economic activity in the long run.